How Employees’ Engagement Mediates Relationship between Transformational Leadership and Employee Performance: Case of Private Universities in Mongolia - Gankhuyag, Gantugs; Zanabazar, Altanchimeg; Baljinnyam, Enkhtuya; Dondog, Jagralmaa (Advances in Social Sciences Research Journal, 2025)
In today’s competitive environment, effective leadership requires quickly adapting to situations, listening to and respecting others’ opinions, incorporating them into one’s actions, collaborating with others, and involving them in decision-making, rather than simply managing and controlling. This study explores the connection between transformational leadership, employee engagement, and employee performance in the context of two private universities in Mongolia. Using a sample of 114 employees, the research investigates how transformational leadership influences employee performance, with employee engagement acting as a mediator. Data were collected through surveys, and structural equation modelling (PLS-SEM) was employed to analyze the relationships among the variables. The results confirm that transformational leadership positively impacts employee performance and engagement, with employee engagement mediating the relationship between leadership style and performance. The study’s findings indicate that fostering employee engagement through transformational leadership enhances both individual and organizational performance. Practical implications suggest that universities should prioritize leadership development programs focusing on transformational leadership qualities to improve employee performance. The research contributes to the growing literature on leadership and employee performance, highlighting the importance of leadership in creating a work environment that promotes engagement and, ultimately, improved productivity.